ONLINE TIKET WEEK, STRATEGI PEMASARAN UNTUK MENINGKATKAN ANTUSIASME PELANGGAN TIKET.COM - Nurshal Shabila Mantika; Anisatul Auliya; Diani Mustika Prianti (Journal of Tourism Destination and Attraction, 2022)
Industry 4.0 is a revolution with exponential speed. In addition, Industry 4.0 enables billions of people to connect and access unlimited knowledge with mobile devices with unprecedented computing power and storage capacity. This study aims to explain and describe the marketing strategy of the "Online Tiket Week" to increase customers' enthusiasm for Tiket.com and to provide information on the sales status of Tiket.com products after the implementation of the marketing strategy. This research used descriptive qualitative methods. This research shows that the "Online Tiket Week" marketing strategy can increase customer enthusiasm and sales at Tiket.com. The marketing activities carried out are known to be very innovative and quite diverse. In addition, "Online Tiket Week" was carried out during the COVID-19 pandemic so the usage of digital platforms has become a suitable advertising approach to do.